Best Answer

Because without an equality sign it is not an equation but it is an algebraic expression.

Q: 2 over 3 x-4 over 5 y plus 3 over 4x plus 3 over 10 why?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Answer this question…A. x4 + 2x3 + 9x2 + 4 B. x4 + 4x3 + 9x2 + 4 C. x4 + 2x3 + 9x2 + 4x + 4 D. x4 + 2x3 + 9x2 - 4x + 4

The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2

(x4 - 2x3 + 2x2 + x + 4) / (x2 + x + 1)You can work this out using long division:x2 - 3x + 4___________________________x2 + x + 1 ) x4 - 2x3 + 2x2 + x + 4x4 + x3 + x2-3x3 + x2 + x-3x3 - 3x2 - 3x4x2 + 4x + 44x2 + 4x + 40Râˆ´ x4 - 2x3 + 2x2 + x + 4 = (x2 + x + 1)(x2 - 3x + 4)

Um.. your question is kinda vague... but I'm gonna assume your question is 4x+11X2+10... so you have to use the order of operations. multiplication first... so 11X2 is 22, making the equation 4x+22+10. Then, add 10 and 22 together, making the equation 4x+32. you don't know what 'x' is, so that's as far you can simplify the equation. So the answer to you question is 4x+32.

10x2 +4x + 21 = 0=> 4*x +10*x^2 +21 = 0Complex roots:Root 1: -0.2-1.435 * iRoot 2: -0.2+1.435 * i

Related questions

Answer this question…A. x4 + 2x3 + 9x2 + 4 B. x4 + 4x3 + 9x2 + 4 C. x4 + 2x3 + 9x2 + 4x + 4 D. x4 + 2x3 + 9x2 - 4x + 4

Limx→0 [ 1 / (x - 4) + 1 / (x + 4) ] / x = Limx→0 1 / (x2 - 4x) + 1 / (x2 + 4x) = Limx→0 (x2 + 4x) / (x4 - 16x2) + (x2 - 4x) / (x4 - 16x2) = Limx→0 (x2 + 4x - 4x + x2) / (x4 - 16x2) = Limx→0 2x2 / (x4 - 16x2) = Limx→0 2 / (x2 - 16) = 2 / (0 - 16) = -1/8

(x^2 + 1)(x^2 - 4x + 13)

The answer to x4+x3-14x2+4x+6 divided by x-3 is x3+4x2-2x-2

X4.

4X + 2x = 1. Where x = 0.166666666666666666666666666666666666666 recurring.

(x4 - 2x3 + 2x2 + x + 4) / (x2 + x + 1)You can work this out using long division:x2 - 3x + 4___________________________x2 + x + 1 ) x4 - 2x3 + 2x2 + x + 4x4 + x3 + x2-3x3 + x2 + x-3x3 - 3x2 - 3x4x2 + 4x + 44x2 + 4x + 40Râˆ´ x4 - 2x3 + 2x2 + x + 4 = (x2 + x + 1)(x2 - 3x + 4)

If you mean -6+4x-5 then the given expression can be simplified to 4x-11 and the unknown variable is x

Um.. your question is kinda vague... but I'm gonna assume your question is 4x+11X2+10... so you have to use the order of operations. multiplication first... so 11X2 is 22, making the equation 4x+22+10. Then, add 10 and 22 together, making the equation 4x+32. you don't know what 'x' is, so that's as far you can simplify the equation. So the answer to you question is 4x+32.

10x2 +4x + 21 = 0=> 4*x +10*x^2 +21 = 0Complex roots:Root 1: -0.2-1.435 * iRoot 2: -0.2+1.435 * i

X^4 ? 4x^3

k = 7 x^4 - 5x^3 + 7x^2 + 3x - 10 = (x + 1)(x - 2)(x^2 - 4x + 5)